Measurement of Personality Structure by the OPD Structure Questionnaire Can Help to Discriminate Between Subtypes of Eating-Disorders - Rohde, Jens; Hofmann, Tobias; Voigt, Barbara; Rose, Matthias; Obbarius, Alexander (Frontiers in Psychology, 2019)
Background: Differentiation between purging type (AN-P) and restricting type (AN-R) is common in anorexia nervosa (AN) and relevant for clinical practice. However, differences of personality pathology in eating disorders (ED) and their subtypes, which can be captured by the operationalized psychodynamic diagnosis (OPD) system, have not been systematically investigated to date. Objectives: The aim of this study was to explore differences in personality structure between the subtypes of AN and bulimia nervosa (BN) using the OPD structure questionnaire (OPD-SQ). In addition, the ability of the instrument to support the classification of eating disorders was examined. Materials and methods: We conducted a retrospective, exploratory study in a subset sample of a larger validation study. The OPD-SQ had been collected from n=60 patients with AN or BN. Patients were assigned to the ED groups by clinical assessment. Statistical analyses included multivariate analysis of variance (MANOVA) and discriminant analysis. Results: Differences between ED groups were observed on 5 OPD-SQ main scales and 9 subscales, as well as on the global scale. AN-P patients demonstrated the lowest personality structure on most of the main scales and subscales, whereas AN-R patients showed a higher personality structure level as compared to both BN and AN-P patients. The OPD-SQ scales with the largest differences include self-perception, object perception, and attachment to internal objects. Discriminant analysis resulted in satisfactory assignment to ED groups by OPD-SQ subscales. Conclusions: Personality structure was found to be less developed in patients with BN and AN-P as compared to patients with AN-R. Although the results have to be proven in larger prospective studies, these results suggest that the OPD-SQ may be used to support the clinical assessment and classification in patients with EDs.